The Expansion of Islam in Pattani, South Thailand: A Historical Analysis - Manan, Abdul; Armi, Fadhlur Rahman; Amri , Wan Yunil (Journal of Al-Tamaddun, 2022)
This qualitative study depicts the dissemination of Islam in Pattani, South Thailand, starting from its earlier Hindu-Buddhist kingdom to the current state, by focusing on the influence of Acehnese Muslims in the progress. Studying related documents and conducting observable behavior for six months toward the local Pattanians also were deployed to enrich the data. The intertwined connections between Aceh and Pattani were identified by the existence of resembling tombstones from Aceh on the Pattanian kings, the Story of Pattani and the Pasai village. In addition, the Muslim ambassadors also contributed to the development of Islam in Pattani. An Acehnese pious scholar, Sheikh Said and the fame Pattanian scholar, Sheikh Daud al-Fatani, played a substantial role in modeling Islam within the Pattani Kingdom and its civilians, even though the position of Islam is inferior compared to Buddha’s throughout Thailand.